Curriculum Management in Islamic Religious Education in Madrasah Ibtidaiyah Negeri - Telaumbanua, Irda Sukma Murni; Nahar, Syamsu; Hanum, Azizah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purpose of this research is to learn more about the Curriculum Management of Islamic Education Subjects in Improving the Quality of Teacher Learning at Madrasah Ibtidaiyah Negeri 1 Gunung Sitoli City. The descriptive qualitative approach was used in this research, which is research that seeks to describe a condition, nature, characteristic, of a phenomenon or research object, or only describes as it is about a variable, symptom, or condition. This method seeks to describe, narrate, and interpret existing social reality phenomena using data gathered from observations, interviews, and documentary studies. The collected data is validated using data validity standards such as credibility by observation, transferability by analyzing the data that has been researched, reliance on checking techniques, analyzing and confirming the data studied, and firmness in classifying the data obtained. done twice, once on the first team and once on the second team The vision and mission of the madrasa serve as the foundation for implementing curriculum planning for PAI subject clusters at MIN 1 Gunung Sitoli City. (2) The curriculum for PAI subject clusters at MIN 1 Gunung Sitoli City is divided into two levels, structural and class, by adhering to the standard operating procedures that have been established. The PAI subject cluster curriculum is organized by integrating all components of the PAI subject cluster curriculum while focusing on the madrasah's vision and mission.